THE STRUGGLE OF A WOMEN IN REALIZING HER MENTAL WEAKNESS IN ZARA ZETTIRA’S NOVEL "EVERY SILENCE HAS A STORY" - Harthaty, Indrie; Rahmat, Aceng; Rasyid, Yumna (IJLECR (International Journal of Language Education and Cultural Review), 2017)
The objective of this research is an analysis of a novel by Zara Zettira entitled "Every Silence has a Story". The novel, which is wrote by adapted of Zara Zettira live itself and with the fictionâ€™s factorâ€™s.Qualitatifapproah with analyziz content method. This novel describe about the womanâ€™s struggle in solving her live problems. The problems of her research are (1) what are her confrontation with the problems in her adult life? (2) What are the influence of her childhood situation to her life? (3) What are her ways in coping with the problems? The writer discusses those problems by using psychological and sociological approach. The writer finds the theories and data that would make the proven by using a library research way and browsing in the internet. The results of her analysis are: (1) she tried to find Factors of Zaira’s silence (2) The influence of Zaira’s childhood situation to her adult stages then and (3) Last, the adaptation to Zaira’s complicated life.